2014
DOI: 10.1002/elps.201400014
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker discovery for neuroendocrine cervical cancer

Abstract: Neuroendocrine cervical cancer is an aggressive but rare form of cervical cancer. The majority of neuroendocrine cervical cancer patients present with advanced-stage diseases. However, the limited numbers of neuroendocrine tumor markers are insufficient for clinical purposes. Thus, we used a proteomic approach combining lysine labeling 2D-DIGE and MALDI-TOF MS to investigate the biomarkers for neuroendocrine cervical cancer. By analyzing the global proteome alteration between the neuroendocrine cervical cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Comparative analysis of the secretome revealed 67 differentially expressed proteins, out of which 36 were also identified as differentially expressed in our study. Furthermore, Lin et al (51) proposed several putative biomarkers for the rare and very aggressive type of neuroendocrine cervical cancer by comparing the proteomic profile of HM-1, a neuroendocrine cervical cancer cell line, to CaSki, ME-180, and HeLa, that exhibit a non-neuroendocrine origin (51). Their study disclosed 82 differentially expressed proteins and further confirmed the differential expression of transgelin, galectin-1 and PGK-1 in all cell lines employing western blotting.…”
Section: Discussionmentioning
confidence: 95%
“…Comparative analysis of the secretome revealed 67 differentially expressed proteins, out of which 36 were also identified as differentially expressed in our study. Furthermore, Lin et al (51) proposed several putative biomarkers for the rare and very aggressive type of neuroendocrine cervical cancer by comparing the proteomic profile of HM-1, a neuroendocrine cervical cancer cell line, to CaSki, ME-180, and HeLa, that exhibit a non-neuroendocrine origin (51). Their study disclosed 82 differentially expressed proteins and further confirmed the differential expression of transgelin, galectin-1 and PGK-1 in all cell lines employing western blotting.…”
Section: Discussionmentioning
confidence: 95%
“…Colloidal Coomassie blueG‐250 staining was used to visualize CyDye‐labelled protein features in 2DE followed by performing interesting post‐stained gel pieces for MALDI‐TOF MS identification. The detailed procedures for protein staining, in‐gel digestion, and MALDI‐TOF MS analysis, and the algorithm used for data processing have been described in previous publication 16,17 . Peaks in the mass range of m/z 800‐3000 were used to generate a peptide mass fingerprint that was searched against the Swiss‐Prot/TrEMBL database (released on February 2014) with 542503 sequences using Mascot software v2.5.0.1 (Matrix Science).…”
Section: Methodsmentioning
confidence: 99%
“…The CaSki cell line is a human cervical cancer cell line that is widely used in cancer research. Several 2-DEproteomics-based studies searching for biomarkers, as well as studies describing the effect of cancer drugs have used the CaSki cell line [55][56][57]. However, there are few reports on the comprehensive characterization of the proteome of this HPV-16 positive human carcinoma compared to the in-depth proteome characterization of Hela, an HPV-18 positive human cervical carcinoma cell line [11].…”
Section: Caski Proteomementioning
confidence: 99%